Racial differences in setting of implantable cardioverter-defibrillator placement in older adults with heart failure and association with disparate post-implant outcomes - Akhabue, Ehimare; Kuhrt, Nathaniel; Gandhi, Poonam; Rua, Melanie; Shalmon, Uri; Visaria, Aayush; Jackson, Larry R; Setoguchi, Soko (Frontiers in Cardiovascular Medicine, 2023)
Background: Implantable Cardioverter-Defibrillator (ICD) placement in heart failure (HF) patients during or early after (≤90 days) unplanned cardiovascular hospitalizations has been associated with poor outcomes. Racial and ethnic differences in this "peri-hospitalization" ICD placement have not been well described. Methods: Using a 20% random sample of Medicare beneficiaries, we identified older (≥66 years) patients with HF who underwent ICD placement for primary prevention from 2008-2018. We investigated racial and ethnic differences in frequency of peri-hospitalization ICD placement using modified Poisson regression. We utilized Kaplan-Meier analyses and Cox regression to investigate the association of peri-hospitalization ICD placement with differences in all-cause mortality and hospitalization (HF, cardiovascular and all-cause) within and between race and ethnicity groups for up to 5-year follow-up. Results: Among the 61710 beneficiaries receiving ICDs (35% female, 82% White, 10% Black, 6% Hispanic), 44% were implanted peri-hospitalization. Black [adjusted rate ratio (RR) 95% Confidence Interval (95% CI): 1.16 (1.12, 1.20)] and Hispanic [RR (95% CI): 1.10(1.06, 1.14)] beneficiaries were more likely than White beneficiaries to have ICD placement peri-hospitalization. Peri-hospitalization ICD placement was associated with an at least 1.5x increased risk of death, 1.5x increased risk of rehospitalization and 1.7x increased risk of HF hospitalization during three-year follow-up in fully adjusted models. Although Black beneficiaries with peri-hospitalization placement had the highest mortality and readmission rates one-and three-years post-implant (log-rank p<0.0001), the magnitude of the associated risk did not differ significantly by race and ethnicity (p=NS for interaction). Conclusions: ICD implantation occurring during the peri-hospitalization period was associated with worse prognosis and occurred at higher rates among Black and Hispanic compared to White Medicare beneficiaries with HF during the period under study. The risk associated with peri-hospitalization ICD placement did not differ by race and ethnicity. Future paradigms aimed at enhancing real-world effectiveness of ICD therapy and addressing disparate outcomes should consider timing and setting of ICD placement in HFrEF patients who otherwise meet guideline eligibility.